Effect of titanium doping on conductivity, density of states and conduction mechanism in ZnO thin film - Jamil, Arifa (2021)
High quality, ~ 120 nm thin ZnO and Ti-doped ZnO (TZO) films were deposited on silicon substrates using magnetron co-sputtering technique. Surface roughness of the films was ~ 2 nm. Ti incorporation effect on the structure, morphology, conductivity, density of states (DOS) and conduction mechanism was investigated in detail. Ti ions were incorporated in the interstitial sites of hexagonal ZnO lattice. Average crystallite size increased from ~ 16.63 to ~ 19.08 nm upon Ti doping in ZnO film. Conduction mechanism changed from overlapping large polaron tunneling (OLPT) for undoped ZnO film to corelated barrier hopping (CBH) for TZO film. The experimental data were fitted theoretically using OLPT and CBH models to calculate frequency and temperature-dependent DOS. An enhancement of ac conductivity and DOS was observed with the doping of Ti in ZnO thin film. Complex modulus study of TZO film revealed transition from long-range mobility to short-range mobility with increase in frequency.